PENERAPAN MODEL PEMBELAARAN INKUIRI PADA MATERI SIFAT-SIFAT BENDA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Dahlia, Desi; Panjaitan, Regina Lichteria; Djuanda, Dadan (Jurnal Pena Ilmiah, 2017)
The research aimed to improve teacher performance in the planning stage is also in the implementation stage, increasing student activity and student learning outcomes. This research is done by applying inquiry model of learning. This inquiry study can help solve the problems that occur in science learning, especially in the material properties of objects. The subject of this research is the fourth grade students of elementary school of Lembursitu. The method used in this research is classroom action research using observation guides, interview guides, field notes and tests as research instruments. This study lasted for three cycles because the new targets were achieved in the third cycle. The target is determined on the performance of teachers is 100%, while the activity and learning outcomes of students is 90%. Based on the results of research proved that learning science can create a conducive atmosphere because students are active in learning. Students are also able to find their own knowledge that makes learning more meaningful. In addition, teacher performance is also increasing with the application of inquiry learning.